Capital social e qualidade de vida em adolescentes trabalhadores em um município de médio porte de Minas Gerais, Brasil - Ana Cristina Viana Campos (2010)
There are few studies of adolescent workers, so this research aimed to measure social capital and its possible relationship with the quality of life among adolescent workers. This was an analytical cross-sectional study with 363 adolescent workers assisted by a Philanthropic entity. The socio-demographic characteristics assed questions regarding sex, age, skin color, and basic sanitation (water supply, presence of toilet in the home, sewage, garbage collection). Information about access / use of health services related to the possession of health insurance, regular use of the public health, public service type most used and number of physician visits in the last 12 months. The instruments used were the Portuguese short version in of the Integrated Questionnaire for Measuring Social Capital (SC-IQ) of the World Bank and the shortened Portuguese version in of the World Health Organization Quality of Life Bref (WHOQOL-Bref) to measure quality of life. Initially, the scores of each domain of WHOQOL-Bref were calculated. The SC-IQ provides no type of scoring, so we used segmentation analysis, canonical discrimination and nearest neighbor interpolation. Results from this study demonstrate that higher social capital scores higher quality of life of adolescents. This means that for the population studied it was possible to verify a positive relationship between these two concepts, even considering the social context in which participants are inserted. The adolescents can spend much of his time in the Philanthropic entity creating a space of opportunities for follow up of adolescents in order to contribute to the growth and development. Further studies may help in the investigation of differences in quality of life and stock of social capital among the workers and those not working so that intervention programs can be deployed.